Penerapan Kompres Hangat Pada Lansia Pada Penurunan Nyeri Gout Arthithis di Puskesmas Sukoharjo - Wulan Agustin Nur Eka; Maryatun Maryatun (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: The prevalence of gouty arthritis has increased significantly by 2023, reaching 33.3% according to WHO. In Indonesia, 35% of cases occur in men aged over 45 years, while Central Java has a prevalence of 26.4%. In Sukoharjo District, Mandan Village recorded the highest number of gout patients with 150 cases, followed by Gayam (75 cases) and Sukoharjo (35 cases). The use of warm water compresses is recommended to relieve joint pain due to gouty arthritis by increasing blood flow and reducing joint stiffness. Objective: Knowing changes in the pain scale in two respondents with gouty arthritis before and after a warm compress method: This research is applied research with a case study using pre-post test results: There was a decrease in Mrs. S's pain scale which initially 6 decreased to 3 while in Mr. T, the pain scale 7 decreased to 5. Mr. T is a pain scale of 7 decreasing to 5. Conclusion: After the application of warm compresses on Mrs. S and Mr. T, there was a decrease in the pain scale. T there is a decrease in the pain scale. Mrs. S from moderate pain to mild pain, Mr. T from severe pain to moderate pain. T from severe pain to moderatepain. This shows that warm compresses can reduce pain in people with gout.